2014
DOI: 10.1007/s00520-014-2334-9
|View full text |Cite
|
Sign up to set email alerts
|

The dyadic effects of coping and resilience on psychological distress for cancer survivor couples

Abstract: Purpose This study aimed to examine the actor and partner effects of coping and resilience characteristics on psychological distress in cancer survivors and their spouses and to examine the mediating role of resilience characteristics in the relationship between coping and psychological distress. Methods A total of 91 breast, colorectal, and prostate cancer survivor-spouse dyads were recruited from the University Hospital registry in Cleveland, Ohio. Standardized questionnaires that assessed psychological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 35 publications
2
85
1
5
Order By: Relevance
“…This does not mean that our results are inconsistent with previous studies, which suggested that social support could buffer against stress and independently reduce cancer-related distress in family caregivers of patients with cancer [16,17]. It must be noted that these studies did not include psychological resilience, which has multiple relationships with perceived social support [39]. Furthermore, our results are comparable to King's [33,40] studies showing that social support was not strong enough to be considered a significant contributor when competing with the other predictors of PTSD among veterans.…”
Section: Discussioncontrasting
confidence: 94%
“…This does not mean that our results are inconsistent with previous studies, which suggested that social support could buffer against stress and independently reduce cancer-related distress in family caregivers of patients with cancer [16,17]. It must be noted that these studies did not include psychological resilience, which has multiple relationships with perceived social support [39]. Furthermore, our results are comparable to King's [33,40] studies showing that social support was not strong enough to be considered a significant contributor when competing with the other predictors of PTSD among veterans.…”
Section: Discussioncontrasting
confidence: 94%
“…Such adverse effects need to be handled in the context of a sexual relation ship, in which each partner holds their own needs and expectations. [31][32][33] Suggesting that time alone, or a single medical intervention alone, will allow the couple to 'get back to normal' can set up unrealistic expectations that lead to disappointment and failure. We have observed that with appropriate support and guidance, and persistence in the use of ED treatments, many couples do resume satisfy ing sexual activity.…”
Section: Introductionmentioning
confidence: 97%
“…The acceptance of unspontaneous sex and sexual aids by some of the patients in this study sample is a particular sign of resilience, given the fact that the literature has shown that men do not use sexual aids and consider erections necessary to satisfying sexuality [36,37]. Research on couples' resilience suggests that the patient's resilience has a positive effect on the partner and leads to positive coping of the couple [38]; studies on both heterosexual and gay men with prostate cancer corroborate the importance of the patient's attitude in suggesting that some men can respond to the challenge of coping with prostate cancer by feeling empowered to identify what is important in their lives and develop compassion for others [39,40]. Drawing on the family therapy literature, Walsh's systems model of resilience tells us that couples who have had a long history together, value their commitment, and have good communication are more likely to adapt to change and adverse health conditions [41].…”
Section: Discussionmentioning
confidence: 84%